THE PREVENTION REVIEW OF CHEMICALS THE MISUSE AS CHEMICAL WEAPONS IN THE ACT OF ATTACK IN INDONESIA - Dewi Sulistyowati; Ivan Yulivan; Satriani Aga Pasma; Rahmana Emran Kartasasmita (Journal Civics And Social Studies, 2023)
In arious regions of the orld ared conflicts occur and cause assie casualties in addition to hsical destruction eaons of Mass estruction M or coonl referred to as eaons of ass destruction hae ecoe one of the ost feared eaons ith the eergence of cheical nuclear radiological iological and elosie eaons Actuall the use of eaons of ass destruction has een anned ut their roduction reains unsuerised alloing soe arties such as terrorists to use easil aailale ra aterials for cheical eaons such as riacetone rieroide A to ake os and the like In addition cheical eaons hose circulation in liuid and gaseous for is not onitored the heical eaons onention ose a risk of longter daage such as eranent urns or diseases that continue to lague their ictis een after the ar ends he folloing eents are certainl a threat to national securit that can e caused irresonsile eole ho hae access to cheicals or socalled Man Made isasters herefore it is necessar to reent siilar eents to iniie the daage the cause his research as conducted through indeth interies and secondar data analsis his research ais to anale the strateg of reenting cheicals that can e used as cheical eaons through the suerision of La o of he results shoed that the regulation of the suerision of cheicals used as cheical eaons is still not effectie and the ulnerailit of Indonesias ide circulation of cheicals So it is necessar to otiie the role of all releant stakeholders to for suerision of the cheical industr in Indonesia fro the threat of dual use.